A dominant contribution to light absorption by methanol-insoluble brown carbon produced in the combustion of biomass fuels typically consumed in wildland fires in the United States. Issue 2 (5th January 2022) - Atwi, Khairallah; Cheng, Zezhen; El Hajj, Omar; Perrie, Charles; Saleh, Rawad
Abstract : Even though the majority of brown carbon in biomass-burning emissions is soluble in methanol, the methanol-insoluble fraction dominates light absorption at mid-visible wavelengths. Abstract : The light-absorption properties of brown carbon (BrC) are often estimated using offline, solvent-extraction methods. However, recent studies have found evidence of insoluble BrC species that are unaccounted for in solvent extraction. In this work, we produced carbonaceous aerosol particles from the combustion of three biomass fuels (pine needles, hickory twigs, and oak foliage). We utilized a combination of online and offline measurements and optical calculations to estimate the mass fractions and contribution to light absorption by methanol-soluble BrC (MSBrC), methanol-insoluble BrC (MIBrC), and elemental carbon (EC). Averaged over all experiments, the majority of the carbonaceous aerosol species were attributed to MSBrC (90% ± 5%), while MIBrC and EC constituted 9% ± 5% and 1% ± 0.5%, respectively. The BrC produced in all experiments was moderately absorbing, with an imaginary component of the refractive index ( k ) at 532 nm ranging between 0.01 and 0.05. However, the k values at 532 nm of the MSBrC (0.004 ± 0.002) and MIBrC (0.211 ± 0.113) fractions were separated by two orders of magnitude, with MSBrC categorized as weakly absorbing BrC and MIBrC as strongly absorbing BrC. Consequently, even though MSBrC constituted the majority of the aerosol mass, MIBrC had a dominant contribution to light absorption at 532 nm (72% ± 11%). The findings presented in this paper provide support for previous reports of the existence of strongly absorbing, methanol-insoluble BrC species and indicate that relying on methanol extraction to characterize BrC in biomass-burning emissions would severely underestimate its absorption.